DEPOSITORY AGREEMENT - Abdreymov Yusupbay Turdibaevich; Dawletmuratova Nargiza Bakhitbayevna (Bright Mind Publishing, 2025)
The deposit agreement is discussed based on information about its significance, content, and concept in civil legal relations. Furthermore, general concepts regarding the object, subject, term, and price of a storage agreement, as well as the grounds for their practical application. Several types of these contracts have been identified in practice, and their distinctive features that distinguish them from other contracts are highlighted. For the purpose of a comprehensive study of the safekeeping agreement, the specific features of the safekeeping agreement in the Civil Code of a foreign country, namely France, were additionally studied.
Keywords: Depository agreement, custodian, consignor, legal characteristics, object, subject, term, price, rights and obligations of the parties, types of depository agreements, pawnshop storage, garment storage, hotel storage, transport organization warehouses, and sequestration.